(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
The increasingly dynamic, complex, and unpredictable business environment has driven companies to transform their approach to risk management. Enterprise Risk Management (ERM), which previously functioned as an integrated risk management framework, is now considered insufficient when implemented in a static and compliance-oriented manner. This study aims to analyze the need for transforming ERM toward a more adaptive model capable of responding to modern risk dynamics. This research employs a qualitative approach through a literature review that examines prior studies published between 2015 and 2024 related to ERM, traditional risk management, and adaptive risk governance in the digital era. The review findings indicate that ERM plays a strategic role in supporting value creation and corporate governance; however, its implementation still faces several challenges, including limited integration of risk data, insufficient digital capabilities, and procedural-oriented risk oversight. The results highlight the necessity of transforming ERM into an adaptive model characterized by process flexibility, technological enablement, real-time risk information updates, and an organizational culture that is responsive to uncertainty. This study is expected to provide academic contributions to the development of the adaptive ERM concept and serve as a reference for organizations seeking to enhance resilience and risk management capabilities amid global risk dynamics.